Experimental Study on Ultimate Strength of Steel Tube Column Filled with Reactive Powder Concrete - Bahaa Al-Abbas; Zainab M.R. Abdul Rasoul; Dhafer Hasan; Sajjad E. Rasheed (Civil Engineering Journal, 2023)
Composite concrete Filled Tubular Steel (CFT) members, which have excellent deformability due to the well-known confined and constrained interaction between steel tube and concrete, have largely been utilized as bridge piers or columns in high-rise buildings, resulting in increased strength and decreased column size. This study examined the experimental performance of steel tube columns filled with reactive powder concrete (RPC) under axial compression. Three sets of columns were used in the experiment, each with variations in shape (square, rectangular, and circular), length-to-diameter ratio, and compressive strength of the RPC. The first set consisted of five columns, while the second and third sets each had seven columns with three different lengths (750 mm, 600 mm, and 450 mm) and two different compressive strengths (54 and 92 MPa). A new numerical model was developed to calculate the ultimate failure load of the columns by considering factors such as the yield strength of steel, the compressive strength of concrete, the column shape, and the ratio of concrete to steel. This model was validated by comparing the results obtained from the experiments to those predicted by the model, as well as by designing equations from various codes. The results showed that the proposed numerical model accurately predicted the ultimate failure load for columns filled with different types of concrete, especially for RPC, while maintaining conservatism compared to the ACI, AISC, and EN codes equations. Doi: 10.28991/CEJ-2023-09-06-04 Full Text: PDF